Desenvolvimento de processo de zeólita A utilizando o caulim da Amazônia e aplicação na adsorção de Cu+2 - MORAES, Cristiane Gomes (Universidade Federal do Pará, 2017)
Around the world millions of tons of inorganic waste are produced every day in mining and mineral processing. These wastes are stored in sedimentation basins or discarded in landfills, and very often are thrown directly into the environment without any treatment process. However, alternative recycling and/or reuse should be investigated and, where possible. This work shows studies in order to reuse the kaolin waste from Amazon, from a kaolin processing company for paper covering. For the synthesis of the zeolite in static and dynamic hydrothermal processes, was used as the silicon source and the aluminum kaolin waste, which passed through the calcination procedure in a muffle at 600°C to obtain metakaolin; and as sodium source chose to 5M sodium hydroxide solution. In the static method was used stainless steel autoclaves, in an oven at 110°C, using 1,75g of metakaolin, varying the time of synthesis and the mass of sodium hydroxide and the dynamic process, we used 100g of metakaolin, mass 34,5g sodium hydroxide; at 95°C under stirring system, varying the time of synthesis, in order to determine the optimal conditions in the synthesis of the zeolite in the process. Matches materials and zeolitic products obtained in the syntheses were characterized by: X-ray diffraction (XRD), scanning electron microscopy (SEM), differential thermal analysis and thermogravimetric (DTA/TG), X-ray fluorescence (XRF) and particle size analysis. There is the possibility of scale-up, since the zeolite obtained, the dynamic process in time of 30 min. Data from adsorption experiments determined by iodometric technique copper alloys and metal and minerals, adjusted by Langmuir and Freundlich suggest that the static and dynamic zeolitic materials have good adsorptive capacity reached 95% efficiency for concentrations in the range of 50 to 100mg/L, thereby demonstrating that these materials are efficient and cost effective alternative when used for the removal of heavy metals, in the case of copper, the treatment of industrial effluents.